A vacancy-engineered Ce-doped NiCo-LDH electrode material for efficient, selective, and stable groundwater defluorination in FCDI systems - Xingtian Wang; Xinyue Jiang; Pengcheng Tang; Junfeng Zhu; Yuwen Wang; Huiqin Li; Dan He; Yuxuan Ma; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2026)

A new species of Leitoscoloplos and redescription of Scoloplos tumidus Mackie, 1991 (Polychaeta, Orbiniidae) from Chinese coastal waters - Yue Sun; Boping Tang; Xinzheng Li (Frontiers in Marine Science, 2026)
We described Leitoscoloplos fangchengensis sp. nov., a new species of orbiniid polychaete from Fangchenggang City, Guangxi Province, Beibu Gulf. The species differs from all congeners by the distinctive membranous pouches located below and posterior to neuropodial lobes on the last thoracic and abdominal chaetigers. We also re−examined material previously identified as Scoloplos marsupialis Southern, 1921 and found that these correspond to Leodamas weizhouensis Sun et al., 2022 and S. tumidus Mackie, 1991. A detailed redescription of S. tumidus Mackie, 1991 was here provided based on Chinese material, together with a table summarizing all known orbinid species bearing membranous pouches. With this study, we are contributing to clarify long-standing taxonomic confusion within Orbiniidae.

Impacts of straw addition on ryegrass (Lolium perenne L.) heavy metal absorption and microbial community structure - Jiuwei Song; Yunxiu Zhao; Yuhan Cai; Boping Tang; Fenghua Ding; Philip C. Brookes; Xingmei Liu (Plant and Soil, 2025)

Biological interactions and soil properties shape bacterial and fungal communities during restoration of Pinus thunbergii shelter in saline soils - Zhugui Wen; Xinyu Liu; Wei Zhou; Xinke Liu; Zhaohan Fan; Yuxuan Wang; Boping Tang; Baoming Ge (Antonie van Leeuwenhoek, 2025)

Indices and methods for evaluating gross ecosystem product in sea areas: a case study in Changdao County, China - Wenwen Li; Shuai He; Erwen Chen; Tao Xia; Yuemei Jin; Boping Tang; Shang Chen (Frontiers in Marine Science, 2024)
Introduction Coastal nations heavily rely on their sea areas to achieve sustainable socioeconomic development. Sea areas offer abundant marine ecosystem products and services that are difficult to substitute with industrial goods. Although considerable research has been performed to evaluate the contribution offrom the marine ecosystems to human well-being, systematic and measurable indices are lacking. Methods To address this knowledge gap, ecosystem service theory was used to establish a framework for assessing the gross ecosystem product (GEP) of a sea area, which represents the total monetary value of final ecosystem products directly and indirectly used by people within a specific administrative jurisdiction in one year. To evaluate marine GEP, three primary indices, i.e., material products, regulating products, and cultural products, were employed, and they consist of eight secondary indices. Material products in the sea area include aquatic products and oxygen products; regulating products include carbon sequestration, climate regulation, waste treatment, and coastal protection; and cultural products include leisure and recreation, and seascape-added value. The marine GEP was calculated for the administrative sea areas of Changdao County, which is located in the Yellow Sea-Bohai Sea transitional zone. Results and discussion Our analysis indicated that from 2017 to 2019, the marine GEP in Changdao ranged between 32.59 and 33.35 billion Chinese yuan (CNY). Regulating products contributed two-thirds of this total value. However, over the three-year period, the marine GEP underwent a 5.64% decrease in Changdao. Specifically, the value of material products increased by 38.85% while that of regulating and cultural products decreased by 9.16% and 15.87%, respectively. Notably, the spatial distribution of ecosystem product values in Changdao displayed two prominent trends: (1) higher values along the coastal sea areas of islands and lower values in offshore sea areas; and (2) higher values in coastal areas of southern islands and lower values in coastal areas of northern islands. Marine GEP may serve as a comprehensive indicator for assessing the sustainability of marine ecosystem. Combining the assessment of both marine and terrestrial GEP facilitates an understanding of how marine and terrestrial ecosystems interact in coastal regions. Furthermore, the combined use of marine GEP and GDP helps better evaluate and sort the level of green development of coastal nations and regions.

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

Whole genome evaluation analysis and preliminary Assembly of Oratosquilla oratoria (Stomatopoda: Squillidae) - Xiaoli Sun; Gang Wang; Jie Yang; Wei Yu; Jiayue Xu; Boping Tang; Ge Ding; Daizhen Zhang (Molecular Biology Reports, 2023)

The Effect of Food Deprivation on Foraging Behavior and Digestive and Metabolic Capacities of the Chinese Mitten Crab, Eriocheir sinensis - Qiaolin Long; Jian Liu; Yunfei Sun; Zhigang Yang; Boping Tang; Yongxu Cheng (Fishes, 2023)
Food deprivation is a common stress in crustaceans that can affect their behavior and physiology. In this study, a video recording analysis system was used to compare the predation rate and behavior of the Chinese mitten crab, Eriocheir sinensis, foraging on the freshwater snail, Bellamya quadrata, under different degrees of food deprivation. The activities of lactate dehydrogenase, α-amylase, pepsin, and lipase in the hepatopancreas of crabs were determined after food deprivation for 0, 3, 9, and 15 days. The results showed that the predation and encounter rates of E. sinensis increased and then decreased with an increase in food deprivation time. The proportion of stationary time of E. sinensis initially decreased and then increased, whereas the proportion of searching and handling time increased initially and then decreased. There was a significant difference in the probability of capture upon encountering; however, food deprivation did not significantly affect the probability of consumption upon capture. Under food deprivation, the proportion of E. sinensis crushing tactics after nine-day food deprivation was significantly lower than that in the first nine days. Lactate dehydrogenase activity in the E. sinensis hepatopancreas after food deprivation was significantly higher than that in those not subjected to food deprivation, and the activities of α-amylase and pepsin in the hepatopancreas were consistent with the predation rate trend, showing an initial increase followed by a decrease. In conclusion, different degrees of food deprivation significantly affected the predation cycle of E. sinensis on B. quadrata. These results lay a solid foundation for further studies on the foraging behavioral ecology of E. sinensis and provide important information for improving E. sinensis production.

Comparative metabolomics analysis of Elodea nuttallii and Cladophora sp. in aquaculture systems - Yongtao Tang; Chen Qian; Liangjie Zhao; Chen Wang; Boping Tang; Xinliang Peng; Yongxu Cheng; Xusheng Guo (Aquaculture, 2023)

Comprehensive Utilization of Land Resources for Photovoltaic Power Generation to Culture Chinese Mitten Crab (Eriocheir sinensis): Growth Performance, Nutritional Composition and Tissue Color - Yangyang Pang; Chao Niu; Lifeng Wu; Yameng Song; Xiaozhe Song; Ao-ya Shi; Xingliang Shi; Zong-wen Wu; Boping Tang; Xiaozhen Yang; Yongxu Cheng (Fishes, 2022)
The assertive growth of photovoltaics (PV) will occupy a lot of land resources. There is also a needed land resource to expand the culturing area of Eriocheir sinensis. The aquavoltaic systems offer a potential solution to integrate PV power and E. sinensis culturing. In this study, we cultured E. sinensis in an area of PV panels (PV group) and an area with no PV panels (control group), respectively. The results showed that the weight gain rate, body length, body width, and meat yield of male crabs in the PV group significantly increases. In addition, the moisture of muscles, hepatopancreas, and testes in the PV group has significantly increased, and the total lipids of the hepatopancreas and muscles in the PV group were significantly decreased. Moreover, the PV panels affected the content of eight amino acids in different tissues, including Met, Arg, Cys, Pro, Gly, Leu, Tyr, and His. In addition, several saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) had been significantly influenced by the PV panels. ∑MUFA, docosahexaenoic acid (DHA), ∑n-3 PUFA, ∑n-6 PUFA, and n-3/n-6 PUFA ratio (p

Two new species of Leodamas Kinberg, 1866 (Annelida, Orbiniidae) from China seas - Yue Sun; Xin Tao; Boping Tang; Xinzheng Li (Journal of Oceanology and Limnology, 2022)

Toxic effects of metal copper stress on immunity, metabolism and pathologic changes in Chinese mitten crab (Eriocheir japonica sinensis) - Dan Tang; Ruobing Liu; Xueling Shi; Chenchen Shen; Yuze Bai; Boping Tang; Zhengfei Wang (Ecotoxicology, 2021)

Identification of putative ingestion-related olfactory receptor genes in the Chinese mitten crab (Eriocheir japonica sinensis) - Chenchen Shen; Dan Tang; Yiping Zhang; Lv Wu; Yaqi Luo; Boping Tang; Zhengfei Wang (Genes & Genomics, 2021)

Comparative transcriptome analysis reveals the expression and characterization of digestive enzyme genes in the hepatopancreas of the Chinese mitten crab - Huayun Guo; Dan Tang; Xueling Shi; Qiong Wu; Ruobing Liu; Boping Tang; Zhengfei Wang (Fisheries Science, 2019)

Comparative transcriptome analysis in the hepatopancreas of Helice tientsinensis exposed to the toxic metal cadmium - Zhengfei Wang; Dan Tang; Linxia Sun; Xueling Shi; Ruobing Liu; Huayun Guo; Boping Tang (Genes & Genomics, 2019)

Mitochondrial OXPHOS genes provides insights into genetics basis of hypoxia adaptation in anchialine cave shrimps - Huayun Guo; Hao Yang; Yitao Tao; Dan Tang; Qiong Wu; Zhengfei Wang; Boping Tang (Genes & Genomics, 2018)

Adaptive evolution of osmoregulatory-related genes provides insight into salinity adaptation in Chinese mitten crab, Eriocheir sinensis - Zhengfei Wang; Yuze Bai; Daizhen Zhang; Boping Tang (Genetica, 2018)

Evolution of mitochondrial energy metabolism genes associated with hydrothermal vent adaption of Alvinocaridid shrimps - Zhengfei Wang; Xuejia Shi; Linxia Sun; Yuze Bai; Daizhen Zhang; Boping Tang (Genes & Genomics, 2017)

Effects of Spartina alterniflora Invasion on the Abundance, Diversity, and Community Structure of Sulfate Reducing Bacteria along a Successional Gradient of Coastal Salt Marshes in China - Jun Cui; Xueping Chen; Ming Nie; Shubo Fang; Boping Tang; Zhexue Quan; Bo Li; Changming Fang (Wetlands, 2017)

Development and characterization of microsatellite loci of Oratosquilla oratoria (Crustacea: Squillidae) - Daizhen Zhang; Ge Ding; Baoming Ge; Huabin Zhang; Boping Tang (Conservation Genetics Resources, 2012)

Structure and variable numbers of tandem repeats (VNTRs) of the mitochondrial control region in mitten crab Eriocheir (Crustacean: Brachyura) - Daizhen Zhang; Ge Ding; Guangyue Wang; Boping Tang; Hongying Sun (Molecular Biology Reports, 2011)

MnHSP90 cDNA characterization and its expression during the ovary development in oriental river prawn, Macrobrachium nipponense - Weihong Zhao; Liqiao Chen; Jianguang Qin; Ping Wu; Fengying Zhang; Erchao Li; Boping Tang (Molecular Biology Reports, 2011)

Isolation and characterization of 10 microsatellite markers in Helice tientsinensis (Brachyura: Varunidae) - Daizhen Zhang; Ge Ding; Huabin Zhang; Boping Tang (Conservation Genetics Resources, 2009)

Effect of ethyl acetate extract from Marchantia convoluta on inhibition of human liver carcinoma HepG2 cells - Hui Cao; Jing Wen Chen; Boping Tang; Ming Xu (Natural Product Research, 2008)